Establishing a culture system that supports in vitro expansion of adult microglia - Subramaiam, Hemavathy; Badiei, Alireza; Ramasamy, Rajesh; Abdullah, Maha; Vidyadaran, Sharmili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: The vast majority of in vitro research on microglia are based on cells isolated from neonatal animals (3-5 days of age). Studying microglia of adults has been limited by the lack of a suitable culture system that supports their growth. In this study, we describe a protocol for growing microglia of adults based on modifications of the technique for culturing microglia isolated from neonatal rats. Methods: Mixed glia isolated from adult rats (age range of 1 month to 3 years old) were seeded in culture flasks coated with poly-L-lysine. Cells were maintained in DMEM media supplemented with insulin-transferrin-selenium (ITS) and recombinant human macrophage colony-stimulating factor (M-CSF). Mild trypsinisation was carried out to isolate microglia from mixed glia culture. Results: Microglia cells of adult rats were successfully grown in vitro. For the expansion of adult microglia, it was observed that coating the cell culture flasks with poly-L-lysine was crucial to encourage cell adherence. The substitution of insulin in culture media with ITS was found to improve cell yield and reduced the number of days required for culture from 28 days to 14 days. Addition of M-CSF to cell culture medium, along with the improvisations described above provided the best adult microglia cell yield (2.91 ± 0.56 × 10 6 cells) compared to the technique of replating cells (0.91 ± 0.65 × 10 6 cells; p<O.O5). Conclusion: Optimisation of primary cell culture technique by coating culture flasks with poly-L-lysine, supplementation of culture medium with ITS and M-CSF allowed microglia of adult rats to be successfully cultured in vitro.